Development of a Progressive Web Application Calculation System for Restaurant Entrepreneurs on Online Food Delivery Platforms - สอนดิษฐ์, ภูธเนตร; โรจนกิจ, ปภินวิทย์; ดีเจริญชิตพงศ์, จิรวิญญ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to: 1) develop a food cost calculation and pricing website as a Progressive Web Application (PWA) capable of accurately processing yield and calculating optimal selling prices to cover platform commission fees (GP/VAT). The application enhances operational efficiency and secures trade secrets through a centralized raw material inventory management system, offline data storage (Local Storage), and a grocery list summary feature that can export data to the LINE application; and 2) evaluate the efficiency and satisfaction of restaurant entrepreneurs regarding the application's use in actual business operations. The sample consisted of 10 small-scale restaurant entrepreneurs operating on food delivery platforms, selected through purposive sampling. The research instruments used for data collection included an efficiency evaluation form by experts and a user satisfaction questionnaire. The statistics used for data analysis were Mean and Standard Deviation (S.D.).            The research results revealed that the web application can accurately process costs and perform reverse pricing calculations (Reverse GP) in accordance with accounting principles. The inventory and grocery list summary functions effectively reduced operational time while ensuring the security of recipe data via the Local Storage system. The overall user satisfaction evaluation was at the highest level (x̄= 4.74, S.D. = 0.46). These findings demonstrate that the developed innovation can effectively resolve the issue of hidden losses and tangibly enhance the management potential of restaurant businesses.